SISTEM INFORMASI PENGELOLAAN RETRIBUSI PASAR DEKON PADA DINAS PERDAGANGAN KABUPATEN LAMPUNG UTARA MENGGUNAKAN METODE PROTOTYPE - Mizan Alkhair; Wartariyus Wartariyus; Ferry Susanto (Jurnal Pepadun, 2022)
The Trade Office is part of the work unit in the structure of the North Lampung Regency Government, one of its functions is to explore potential sources of regional income, as an effort to raise funds, which are intended to handle all funding matters, both for regional development and regional government administration, as a form of form of independent government. One of the potentials that contribute as local revenue for the North Lampung Regency Government is in the sector that comes from market retribution. From the desired target with the realization of the conditions in the field, it turns out that the hope to realize the target is difficult to realize. To address this, it is necessary to have serious attention from the relevant agencies, in this case the North Lampung Regency Government Trade Service, which handles the management of market retribution, in order to find the cause of not achieving the expected market retribution target. For this reason, it is necessary to have an active role from the relevant agencies in managing market retribution income and how to create a sense of awareness from the community (kiosk/lapak owners) as mandatory market retribution payers, so that the local revenue of the North Lampung Regency Government can increase, especially in the market retribution sector. As for the information system in managing the Dekon market retribution at the Trade Office at this time, it is still done traditionally/manually. By using the general ledger in recording revenue data and archiving files it is still a document. As a result, real data on Dekon market retribution income is still less accurate and requires quite a long time in the process of preparing Dekon market retribution income reports for each desired period. Based on the results of field observations, this is due to the frequent lack of clarity on collection officers in the field (because of the lack of good data archiving of employees in the field), kiosk stall data that changes owners from time to time (always updated) and payment proof data that is often lost and damaged. Based on the problems above, the author proposes a system for managing the Dekon market retribution at the Department of Trade, using a computerized system. By using the Visual Basic 2010 application program, in making the application and using the Microsoft Access 2010 application as the database. Hopefully with this computerized system, it is hoped that it can help solve the problems of managing data on the Dekon market retribution that is currently being experienced.